Facebook's ‘white genocide' problem: a sociotechnical exploration of problematic information, shareability, and social correction in a South African context - Barraclough, Jessica Ann (Centre for Film and Media Studies, 2021)
A relatively small, but highly visible group of South Africans believe that farm attacks/murders (and other crimes against whites) constitute a targeted ‘white genocide'. Their beliefs have found support and corroboration in various online spaces, but especially within ‘alternative news' Facebook pages. This case study is used as an opportunity to apply a sociotechnical model of media effects to a very real disinformation problem that continues to inflame race relations in South Africa. Three pivotal questions are addressed, relating to (1) how Facebook users on farm attack/murder-focused pages engage with problematic information (fake news) and why; (2) the qualitative and affordance/format-related themes of posts with the highest share counts on these pages; and (3) the common themes of discourse used in defensive responses to social corrections of false information. Findings suggest that South Africa's ‘white genocide' problem is more deep-set than other more ephemeral ‘fake news' stories, especially due to stark racial and political dichotomies, reflected by the post comment sections herein. Group identities and cognitive biases work to sustain the disproportional media ‘spectacle' of gratuitous farm attacks/murders against white South Africans, and leverage Facebook's platform affordances to do so.